2019
DOI: 10.1038/s41545-019-0030-5
|View full text |Cite
|
Sign up to set email alerts
|

A global review of the microbiological quality and potential health risks associated with roof-harvested rainwater tanks

Abstract: A broad body of literature has been published regarding roof-harvested rainwater quality around the world. In particular, the presence of fecal indicator bacteria and pathogenic microorganisms has raised concerns regarding the acceptability of rainwater for potable and non-potable uses. As the use of molecular assays has improved understanding of the diverse microbial communities present in rainwater tanks and their role in providing benefits or harm to human health, a comprehensive review is needed to summari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 135 publications
2
44
0
4
Order By: Relevance
“…Despite the reported successes of these water disinfection methods, each of them has certain disadvantages that make their use limited or unfavorable in some instances. For example, some Gram-negative spore-formers may require longer exposure time for complete disinfection by SODIS (solar water disinfection); bacterial regrowth after 24 h posttreatment has been reported with SODIS, due to the initiation of photo-associated DNA repair (Hamilton et al 2018). Similarly, added to the regrowth observed with SODIS, disinfection through UV irradiation is considered an expensive alternative and requires extensive and regular maintenance of equipment, while ozonation can also produce hazardous disinfection by-products (Pūle 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the reported successes of these water disinfection methods, each of them has certain disadvantages that make their use limited or unfavorable in some instances. For example, some Gram-negative spore-formers may require longer exposure time for complete disinfection by SODIS (solar water disinfection); bacterial regrowth after 24 h posttreatment has been reported with SODIS, due to the initiation of photo-associated DNA repair (Hamilton et al 2018). Similarly, added to the regrowth observed with SODIS, disinfection through UV irradiation is considered an expensive alternative and requires extensive and regular maintenance of equipment, while ozonation can also produce hazardous disinfection by-products (Pūle 2017).…”
Section: Introductionmentioning
confidence: 99%
“…up to a geometric 240 CFU/ mL for recycled water (USEPA, 2012b)] and risk benchmarks (10 −4 probability of infection or 10 −6 disability adjusted life years per person per year (pppy) in the absence of additional treatment and/or BMPs depending on the area, end use, and source water. Microbial risks from harvested rainwater are considered as captured stormwater but have been reviewed elsewhere (Hamilton et al, 2019).…”
Section: Health Risk Assessment Approachesmentioning
confidence: 99%
“…Yet, some constraints should be pointed out before the harvested rainwater could be used, especially if it is intended to be used for potable uses [15]. Many international studies reported the quality of rainwater is contaminated with various microbial pollutants [16][17][18] and heavy metals originated from raindrops, catchment areas, and storage [19], which requires proper treatment.…”
Section: The Quality Of Rainwater Harvestingmentioning
confidence: 99%